La idea de nacionalismo católico. Algunas aporías conceptuales en textos de autores argentinos - Muñoz, Ceferino; Muñoz, Ceferino (Universidad de Costa Rica, 2022)
Catholic nationalism claims to have the theoretical support of its principles in the same catholic doctrine. In this sense, Thomas Aquinas, considered the Common Doctor of the Church, is usually one of the most cited authors in this regard, especially when he speaks of the virtue of godliness in the “Suma of Theology”. However, in this work attemps to show that at least in the letter of Thomas neither explicitly nor implicitly appears the idea of nationalism as a special form of the virtue of godliness, nor the idea of homeland as understood by some  exponents of Argentine Catholic nationalism.